Dinamika Pendidikan Islam dan Liberalisasi Pendidikan di Indonesia - Abdul Hadi (STAIFAS-Press, 2021)
This paper on the dynamics of Islamic education and the liberalization of education departs from the regulation of Islamic education that entered the vortex of western libelism. Liberalization of education is a new formula to formulate the concept of education ideally so that in the process of teaching and learning a teacher must understand the development of his students critically and sustainably. Islamic education and education liberalization is an attempt to change or reform the order of education so that the world of education is more advanced and provides fresh colors so that Islamic education runs dynamically. Liberalization of education does not mean free but must be in line with islamic educational values that must be adapted to the times so as not to be left behind to keep up with the development of the world of education. While in Islamic education the concept of essence in accordance with the values in the Islamic concept is oriented not only to the world but also at the same time to achieve success, happiness, and benefit in the afterlife. Tulisan ini tentang dinamika pendidikan Islam dan liberalisasi pendidikan hal ini berangkat dari regulasi pendidikan Islam yang masuk pada pusaran libelisme barat. Liberalisasi pendidikan merupakan formula baru untuk merumuskan konsep pendidikan secara ideal sehingga dalam proses belajar-mengajar seorang guru harus memahami perkembangan anak-anak didiknya secara kritis dan berkelanjutan. Pendidikan Islam dan liberalisasi pendidikan adalah suatu usaha untuk merubah atau mereformasi tatanan pendidikan sehingga dunia pendidikan lebih maju dan memberikan warna segar agar pendidikan Islam berjalan secara dinamis. Liberalisasi pendidikan bukan berarti sebebas-bebasnya tetapi harus sejalan dengan nilai-nilai pendidikan Islam yang harus disesuaikan dengan perkembangan zaman sehingga tidak tertinggal untuk mengikuti perkembangan dunia pendidikan. Sementara dalam pendidikan Islam konsep hakiki yang sesuai dengan nilai dalam konsep Islam berorientasi tidak hanya untuk dunia semata melainkan juga sekaligus untuk meraih kesuksesan, kebahagiaan, dan kemaslahatan di alam akhirat.